Putting Stakeholder Management into Practice - Huber, Margit; Scharioth, Joachim; Pallas, Martina (Springer Berlin Heidelberg, 2004)
Stakeholder Management - today's buzzword - is difficult to translate into practice even for the experienced manager. Following "How to achieve excellence in Stakeholder Management", which included case studies from reputable companies, the present volume goes beyond explaining theoretical constructs. Success stories from a wide range of sectors and regions are analyzed in depth in order to illustrate how Stakeholder Management can be tailored to each unique situation. The reader will get concrete answers and ideas about planning and implementing successful stakeholder management in the area of customer retention, employee commitment and internal service quality. These business cases are complemented by articles on the Balanced Scorecard as well as the link between customer satisfaction and business success
Keywords: Business Strategy/Leadership; Leadership; Beziehungsmanagement; Kundenmanagement; Stakeholder; Aufsatzsammlung; Fallstudiensammlung